Recurrent posterior talar osteochondroma in a child managed with medial malleolar osteotomy: a case report - Shilu, Jishnu; Sageer, Mohammad (International Journal of Research in Orthopaedics, 2026)
Osteochondromas are the most common benign bone tumours in children and adolescents. They usually arise from the metaphyseal regions of long bones, and hence involvement of the talus is uncommon. Posterior talar osteochondromas in children are extremely rare and may mimic dysplasia epiphysealis hemimelica (Trevor’s disease). An 11-year-old girl presented with recurrent pain and swelling over the posteromedial aspect of the left ankle following excision biopsy of a similar lesion from the same site 11 months earlier. Radiographs demonstrated a pedunculated exostosis arising from the posterior talus with cortical and medullary continuity. Magnetic resonance imaging showed a 2.5×1.8 cm lesion with a thin cartilaginous cap and no features suggestive of malignancy. The lesion was excised en bloc through a medial malleolar osteotomy approach. The approach provided excellent exposure of the posterior talus and allowed complete removal of the tumour. Histopathology confirmed osteochondroma. At 24-month follow-up the patient was asymptomatic with full ankle range of motion, radiological union of the osteotomy and no evidence of recurrence. The American Orthopaedic Foot and Ankle Society ankle-hindfoot score was 98/100. Medial malleolar osteotomy provides safe and effective exposure for complete excision of recurrent posterior talar osteochondromas in paediatric patients while preserving ankle function.